2022
DOI: 10.3390/agronomy12051202
|View full text |Cite
|
Sign up to set email alerts
|

Seed Coating with Triflumezopyrim Induces the Rice Plant’s Defense and Inhibits the Brown Planthopper’s Feeding Behavior

Abstract: Triflumezopyrim (TFM), a novel mesoionic insecticide, has been effective in controlling sucking insect pests such as the brown planthopper (BPH). However, the mechanism of TFM as a seed coating agent in paddy fields remains unclear. Here, we investigate the seed germination rates (>80%) and seedling emergence rates (>85%) of rice treated with TFM at 0, 22.5, 45.0, 67.5, and 90.0 g a.i. ha−1 with no significant effect on germination rates. In addition, the low TFM residue concentration (0.04 mg. kg−1) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…In addition, the weights of female BPHs fed on DCY100-pretreated plants of two rice varieties were decreased significantly (Figure 8), and these results were consistent with those of a previous study [27]. Recent studies have indicated that treating seeds with triflumezopyrim enhanced rice resistance against BPH by inhibiting phloem ingestion, which resulted in the reduced fecundity of females and lowered the population in the field [42,43]. A two-way ANOVA suggested that the effect of DCY treatment on the honeydew excretions and weights of BPHs was greater than rice variety and the interactions between DCY treatment and rice variety (Table 6).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the weights of female BPHs fed on DCY100-pretreated plants of two rice varieties were decreased significantly (Figure 8), and these results were consistent with those of a previous study [27]. Recent studies have indicated that treating seeds with triflumezopyrim enhanced rice resistance against BPH by inhibiting phloem ingestion, which resulted in the reduced fecundity of females and lowered the population in the field [42,43]. A two-way ANOVA suggested that the effect of DCY treatment on the honeydew excretions and weights of BPHs was greater than rice variety and the interactions between DCY treatment and rice variety (Table 6).…”
Section: Discussionsupporting
confidence: 87%